Accounting for the 'Little Divergence' What drove economic growth in pre-industrial Europe, 1300-1800? - Alexandra M. de Pleijt; Jan Luiten van Zanden (European Historical Economics Society (EHES), 2016)
We test various hypotheses about the causes of the Little Divergence, using new data and focusing on trends in GDP per capita and urbanization. We find evidence that confirms the hypothesis that human capital formation was the driver of growth, and that institutional changes (in particular the rise of active Parliaments) were closely related to economic growth. We also test for the role of religion (the spread of Protestantism): this has affected human capital formation, but does not in itself have an impact on growth.
Keywords: N13; N33; O40; O52; 330; Europe; Economic growth; Little Divergence; Human capital formation